(untitled) (Research, Society and Development, 2020)
Objective: To report the experience of implementing educational practices through Culture Circles, with professionals and users of a Basic Health Unit. Method: This is an experience report that presents the methodological procedures for the development of educational actions based on the Paulo Freire method, Circles of Culture. The research scenario was a Basic Health Unit in the urban area of a municipality in the extreme south of Rio Grande do Sul. The intervention and data collection were developed in the period of December 2014 and August 2016. Results: The report is divided into three interdependent stages: thematic investigation, theme and problematization. The contact to the population during educational activities made it possible to strengthen the bond and allowed the execution of individual and collective care, participatory, continuous and humanized. Final considerations: Health education actions based on the Paulo Freire method provided the articulation of scientific and popular knowledge, teaching and theory, contributing not only to the health education of users, such as improvement and qualification of professional practice, obtaining as the final product of the intervention a better quality of health services.